A semantic document management system for legal applications. (1st December 2008) - Amato, Flora; Mazzeo, Antonino; Penta, Antonio; Picariello, Antonio
Knowledge management in the legal domain has become a challenging issue for e-government-based applications. In this paper, we propose a core for a legal information system that manages a variety of hard paper documents and automatically transforms them into Resource Description Framework (RDF) statements for suitable indexing, retrieval and long-term preservation. Although we describe a general architecture that can be used for several legal application domains, our system is particularly suitable for the notary realm.